Uncharted waters : paying benefits from individual accounts in federal retirement policy - Apfel, Kenneth S. (Kenneth Stephen), 1948-; Graetz, Michael J. (National Academy of Social Insurance, 2005)
In the debate over Social Security reform, most of the work on individual accounts has focused on how individuals would save and manage those accounts during their working lives. Uncharted Waters goes further and addresses the often neglected questions about how and under what circumstances funds could be withdrawn from these accounts. In Uncharted Waters, a panel of recognized experts created a framework for determining how benefits might be paid if private accounts become a new part of the Social Security system or are created separate from Social Security. This important volume analyzes the potential implications of different policy choices. It considers the ramifications of payout rules for families at different stages of life, particularly for economically disadvantaged groups. The contributors also address how any new individual account program would fit with traditional Social Security, employer-based pensions, and tax-advantaged individual retirement savings (401(k)s and IRAs). As the debate over individual savings accounts rages, Uncharted Waters offers a sound framework for informing public policy on both sides of the argument.